(untitled) (Research, Society and Development, 2022)
Blood is a vital resource for any healthcare institution, it is a global challenge to deal with the increased demand and waste of this resource. The objective of this study was to develop and validate an application that analyzes the efficiency of requests for packed red blood cells and directs hemotherapy procedures in elective surgical procedures. An observational, descriptive research with a cross-sectional design was carried out and an application for the management of transfusion of packed red blood cells in surgeries was validated. The application named Banco de Sangue is composed of three independent modules: rate of use of packed red blood cells, rate of transfused patients and maximal surgical blood schedule; the first analyzes the degree of efficiency of the request in relation to a given procedure, the second the hemotherapy procedure and the third the amount of packed red blood cells to be reserved, when necessary. In this way, through a rigorous method of elaboration, an application was developed that aims at the rational use of blood in elective surgical procedures.